Nouveau regard sur l’hôpital de Semur-en-Auxois à travers ses archives du XVIIIe siècle - Pierre Pinon (In Situ)
This article is inspired by a broader context of studies for the creation of a designated conservation area (secteur sauvegardé) at Semur-en-Auxois and a forthcoming publication on the urban and architectural heritage of this town. It offers a description of the hospital during the eighteenth century, based on the archives held today by the departmental archives of the Côte-d’Or department. The hospital is first attested in the town during the twelfth century. In the middle of the eighteenth century, it moved to occupy to former governor’s hôtel, situated in a neighbourhood near the château. The work was carried out between 1745 and 1748 by a little-known local architect, Jacques Lapoton, from Flavigny-sur-Ozerain (Côte-d’Or). The archival sources show us that the building materials were of local origin too, but the masons and stone-cutters came from the Limoges region. The sculptures of the façade of the chapel are by Vincent François and the entrance grill for the courtyard was designed in 1771 by Bénigne Marion.